Ugandan households: A Study of parenting practices in three districts. (May 2017) - Boothby, Neil; Mugumya, Firminus; Ritterbusch, Amy E.; Wanican, Joyce; Bangirana, Clare Ahabwe; Pizatella, Adrienne D.; Busi, Sophie; Meyer, Sarah
Abstract: Ugandan households play a central role in child care and protection, and household-level practices influence the ways in which children are protected from adversities. This study was designed to identify community perceptions of protective and harmful parenting practices in three districts in Uganda. It employed free-listing interviews to determine priorities and practices deemed to be important in providing care and protection to children. Findings suggest that parenting practices can be grouped into seven basic themes, which are: Investing in children's future, Protection, Care, Enterprising, Relationship with neighbors, Intimate partner relationship, and Child Rearing. Investing in children's future, including educating children, was cited most often as a hallmark of positive parenting; while failure to care for children was most often cited as a hallmark of negative parenting. Concrete behaviors, such as walking a daughter to school; sewing a son's torn pants before going to church; and structuring study time at home were identified as concrete actions Ugandan parents undertake daily to promote their children's well-being. Conversely, specific contextual aspects of neglect and abuse were identified as central components of negative parenting, including lack of investment in children's education and not serving as a good role model. Building on community strengths is recommended as a principal means of enhancing household resilience and reducing childhood risk.